The Perspective of Bioterrorism in Asymmetric Warfare and Countering Bioterrorism - Syamiajaya, Arh Nur Afiad; Halkis, Muhammad.; Ahmad G. Dohamid; Muhamad Noor Gibran; Rudy Sutanto; Lukman Yudho Prakoso (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to analyse the Definition and Basic Concepts, Threat Assessment, Dynamics of Bioterrorism Threats, Motivating Factors Driving the Use of Bioterrorism in Asymmetric Conflicts, Legal Perspectives, Impacts and Threats of Bioterrorism in Asymmetric Warfare, and Strategies and Efforts to Counter Bioterrorism. The methodology used in this research is qualitative descriptive with data collection through journals and other publications related to bioterrorism. The research findings indicate that Bioterrorism is the use of biological agents or toxins to cause disease or death in humans, animals, or plants, with the aim of instilling fear, disrupting daily life, or achieving political or ideological goals. These attacks exploit the biological properties of agents such as bacteria, viruses, fungi, or natural toxins, requiring a deep understanding of agents, spread, health impacts, public policies, and national security strategies.